The Traveling Sidewalk: The Mobile Architecture of American Shop Windows at the Turn of the Twentieth Century. (8th November 2016) - Lasc, Anca I
Abstract: This article argues that American window designers at the turn of the twentieth century not only helped shops advertise their wares but also created flexible, unstable and mobile environments which acted upon people's perceptions of the material world around them. As shoppers' eyes turned from sturdy façades to themed displays of mass-produced goods, the 'here' and 'now' of the modern city were replaced with alternative times and spaces that added new 'realities' to the urban grid. The article further examines the emergence of window dressing as a profession and the windows' relationship with the street as trimmers helped create a mobile modern metropolis.